Acquiring Industrial Archives. Reviewing the Greek example - Stoyannidis, Yannis (Journal of Integrated Information Management, 2019)
Purpose - In an era that any information is searched and understood in a digital environment there is still workload to be taken on a physical basis. Small and larger corporations keep abandoning their archives in dark storerooms. In order to bring these stories into the light of history and to broaden the available sources for researchers this article describes the efforts taken on the acquisition and preservation of industrial archives in Greece and discusses the steps that young archivists could follow for enriching business archives deposits. Design/methodology/approach - The text recounts different efforts of managing industrial archives (acquisition, appraisal). This paper is mainly a retrospective that aims to summarize different cases in order to uncover the challenges of this field for young archivists. One of this text’s assets is the discussion about the ways that the archival community has dealt with business archives and what could be done in terms of archives management policy. This article will prove useful to young archivists interested in the process of preserving historical business archives and managing future accruals.